Factors affecting self-directed learning readiness of the undergraduate nursing students from Purbanchal university, Nepal: a cross-sectional study - Koirala, Namu; Kafle, Shyam Prasad; Koirala, Anupam (Journal of Chitwan Medical College, 2021)
Background: Self-directed learning is a higher educational learning paradigm where learners take both learning initiatives and evaluate learning outcomes. Since students have control over their own learning, they can understand their own strengths, interests, limitations and style of receiving new information. The objective of this study was to assess the factors associated with self-directed learning readiness of the undergraduate nursing students from the nursing school of Purbanchal University. Methods: A descriptive, cross-sectional study was conducted from January 2019 - August 2020 among undergraduate nursing students from Purbanchal University School of Health Sciences where 253 students participated. Census sampling method was adopted. Ethical clearance was taken from Institutional Review Committee of Purbanchal University School of Health Sciences. Self-administered, valid and standard tool i.e. Williamson’s Self Rating Scale for Self-directed Learning (SRSSDL) was used. Data was collected using online google forms and analysis was done with SPSS 16.0 version using mean, median, standard deviation, range, chi-square test, and multivariate logistic regression analysis at p<0.05. Results: Overall Self-directed Learning score was 244.58±31.93. Majority of the respondents (79.1%) had high scores of SRSSDL (221-300) and 20.9% of the respondents had moderate scores of SRSSDL (141-220). On bivariate analysis, the marital status of the students (p= 0.025) and grade/division in the previous academic year (p= 0.013) exerted significant association on the overall level of SRSSDL. On multivariate analysis, the unmarried students had 4.298 times higher odds of having higher scores of SRSSDL (AOR: 4.298; CI: 1.28-14.18). Conclusions: Overall self-directed learning readiness among the nursing students was moderate to high. Only the marital status was the significant factor affecting the SRSSDL among the nursing students.